Alteração no padrão de expressão de genes associados ao perfil leucemogênico da leucemia linfóide aguda infantil: antes e depois da quimioterapia de indução - Minasi, Lysa Bernardes (2013)
The ALL is a malignant disorder that originates from a precursor cell lympho-hematopoietic system compromised for the development of B or T lymphocyte lineage.The precursor cell acquisition by a series of genetic abnormalities alters the normal process of maturation leading to cellular differentiation arrest and leukemic clone proliferative advantage on cells of hematopoietic tissue. More than 50 recurrent genetic alterations have been identified in the ALL. These often involve genes known or putative role in the development of lymphocytes and in the case of leukemogenesis.In this study, the variation in the expression of molecular markers was analyzed using PCR methodology array on 16 children with ALL before treatment and at the end of induction chemotherapy (D +28). These patients were diagnosed in HAJ and SCMG, from May 2012 to January 2013. Samples of bone marrow or peripheral blood were sent to NPReplicon-PUC-GO. In the present study we observed a negative correlation between gender and immunophenotype (p = 0.016), females have a greater association with immunophenotype B and less associated with immunophenotype T. We also observed a positive correlation between immunophenotype and age (p = 0.04), immunophenotype and marker CD10 + (p = 0.03), immunophenotype and risk group (p = 0.015) and marker CD10 + and risk group (p = 0.043). Before treatment the gene RUNX1 met with increased expression by 5.0 times compared to the control group and after induction chemotherapy was observed a reduction in its expression. The expression pattern of the gene TAL1 showed significant decrease, with the exception of post-treatment analysis showed that an increase in its expression. A positive correlation was observed between the expression of BAX and BCL2 (r = 0.94 and p <0.0001. We demonstrated a significant difference in gene expression pattern of ALL at diagnosis and after induction therapy. We conclude our observation regarding the gene expression profile in patients with ALL enrolled in this study, but to define a panel of molecular markers is necessary to evaluate several other genes involved in the process of leukemogenesis in ALL with the help of other methodologies.